Computational analysis and characterization of dysregulated chromatin interactions and RNA biology in acute myeloid leukemia - Kong, Lingshi (Nanyang Technological University, 2022)
Cancer is a highly lethal disease. Epigenetics has been found to be influential in cancer biology. Acute Myeloid Leukemia (AML), a disease derived from the aberrant differentiation and proliferation of haematopoietic progenitor cells, has been found to have a tight connection with epigenetics. Here we investigated how chromatin interactions, a type of epigenetic, are dysregulated in AML clinical samples and DNMT3A mutant myeloid leukemia. We obtained and analyzed the 3D genome organization maps through Hi-C in both AML and normal CD34+ clinical haematopoietic stem cells as well as DNMT3A CRISPR knockout K562 cells. Altered chromatin interactions were found in AML and DNMT3A CRISPR knockout K562 cells. A Frequently Interacting Region (FIRE) in the MEIS1 region was found to be absent in half of AML samples (4 of 8) which showed low MEIS1 levels compared with normal samples and AML samples with the FIRE. The CRISPR excision of a CTCF binding site at the border of this FIRE led to MEIS1 expression loss, loss of chromatin interactions between the MEIS1 promoter with enhancers, modulation of H3K27ac levels at enhancers, and reduced cell growth. To address the influence of DNMT3A mutations on chromatin interactions, clinical AML RNA-Seq from an online database was analyzed, which suggested that DNMT3A mutations are associated with dysregulated Topologically Associated Domain (TAD) boundaries. From Hi-C analysis, the loss of two FIREs and two loops were also observed in DNMT3A CRISPR knockout K562 cells, which was associated with downregulation of PLOD2, MACC1, and ARID5B. Further integrated analysis of CTCF and histone mark ChIP-Seq, as well as RNA-Seq, suggested that DNMT3A loss led to altered histone marks, CTCF binding, chromatin interactions, and gene expression. Taken together, our work provided a better understanding of chromatin interactions alterations and gene expression changes in AML and DNMT3A mutant myeloid leukemia. Our research indicates the relevance of chromatin interactions in cancer biology and suggests that drugs that modulate epigenetic, such as DNA methylation, may lead to changes in chromatin interactions. In future research, we are interested to develop therapeutic strategies for altering the dysregulated chromatin interactions seen in AML through epigenetic drugs.